(untitled) (Nepal Journal of Environmental Science, 2021)
The Himalayan musk deer (Moschus leucogaster) is an endangered species listed in the IUCN Red List and Appendix I of CITES. It is widely but discontinuously distributed in Nepal. A Pellet sign survey was carried in April 2019 in Lapchi valley of Gaurishankar Conservation Area (GCA) in Nepal to assess the habitat preference of Himalayan musk deer. A total of 11 transects of 16348 m length and 10 m wide was surveyed. Seven Parameters: Elevation, Aspect, ground cover, distance from the water source, crown cover, rock exposure, and distance from settlement/cow sheds were recorded from the location where pellet (toilet) of musk deer were recorded to extrapolate the probable habitat map. We recorded a total of 157 musk deer pellet groups in the study area14.27 ± 2.91. The study concluded that the 38.4% (26.5 km2) area of Lapchi valley is the probable habitat of musk deer. The c2 – test suggested that the distribution of musk deer is significantly associated with elevation and aspect of the location. Musk deer mostly preferred habitat between 3600-4000 m elevations, with North-West aspect, ground cover less than 25%, and canopy cover between 25%-50%. Musk deer signs were recorded in areas with rock exposure ranging from as low as less than 25%. Distance from the water source and human settlement affect the distribution of musk deer. The indirect signs were higher near water sources and far from human settlement.